Clinical Remission and Psychological Management are Major Issues for the Quality of Life in Pediatric Crohn Disease. Issue 1 (January 2021) - Gourdonneau, Anne; Bruneau, Léa; Ruemmele, Frank M.; Norsa, Lorenzo; Takeda, Armelle; Le Gall, Catherine; Clouzeau, Haude; Rebouissoux, Laurent; Dabadie, Alain; Bridoux-Henno, Laure; Rebeuh, Julie; Thomassin, Nadège; et al.
ABSTRACT: Objectives: Crohn disease (CD) can affect patient's quality of life (QOL) with physical, social, and psychological impacts. This study aimed to investigate the QOL of children with CD and its relationship with patient and disease characteristics. Methods: Children ages from 10 to 17 years with diagnosed CD for more than 6 months were eligible to this cross-sectional study conducted in 35 French pediatric centers. QOL was assessed by the IMPACT-III questionnaire. Patient and disease characteristics were collected. Results: A total of 218 children (42% of girls) were included at a median age of 14 years (interquartile range [IQR]: 13–16). Median duration of CD was 3.2 years (IQR: 1.7–5.1) and 63% of children were in clinical remission assessed by wPCDAI. Total IMPACT-III score was 62.8 (±11.0). The lowest score was in "emotional functioning" subdomain (mean: 42.8 ± 11.2). Clinical remission was the main independent factor associated with QOL of children with CD (5.74 points higher compared with those "with active disease", 95% confidence interval [CI] 2.77–8.70, P < 0.001). Age of patient at the evaluation was found negatively correlated with QOL (−0.76 per year, 95% CI: −1.47 to −0.06, P = 0.009). Presence of psychological disorders was associated with a lower QOL (−9.6 points lower to those without, 95% CI: −13.34 to −5.86, P < 0.0001). Total IMPACT-III and its subdomains scores were not related to sex, disease duration, or treatments. Conclusions: These results not only confirm that clinical remission is a major issue for the QOL of patients, but also highlights the importance of psychological care. Abstract : Supplemental Digital Content is available in the text